Uncovering The Relationships Between Strategic Capability, Strategic Flexibility, And Performance - Evanthi, Ayundha; Azhar, Ratih Mukti (International Journal of Science, Technology & Management, 2023)
Abstract. Strategic flexibility and strategic capability are seen as strategic activities carried out by companies to compete and adapt to the business environment to achieve the expected performance. The objectives of this research are: (1) examine strategic flexibility, strategic capability, and performance by emphasizing their relationships, dimensions and roles of context (2) identify the relationship between strategic flexibility, strategic capability and performance that can be used for future theory development. This research uses bibliometric analysis to map how strategic flexibility, strategic capability and performance intended from several previous journals using VOSviewer. This research concludes that implementing strategic flexibility and strategic capability will result in effective relationships and good firm performance although strategic flexibility is not directly related to the strategic capability. Performance mediates the influence between strategic flexibility and strategic capability. The strategic flexibility is influenced by product innovation, absorptive capacity, and dynamic capability, in the other hand, strategic capability is influenced by network capability. The implication of this research are following researches can add literatures and new theories on the strategic flexibility and strategic capability so that research and discussion on this object can continue to grow. Keywords: Strategic Flexibility, Strategic Capability, Performance